2017
DOI: 10.1371/journal.pone.0183829
|View full text |Cite
|
Sign up to set email alerts
|

For how many days and what types of group activities should older Japanese adults be involved in to maintain health? A 4-year longitudinal study

Abstract: ObjectiveStudies have suggested that frequent participation in social groups contributes to the well-being of older people. The primary aim of this study was to identify the number of days older adults should participate in the activities of social groups to maintain their health for 4 years. This study also aimed to examine whether the effective frequency differs by the type of social group activity.MethodWe examined a prospective cohort of 1,320 community-dwelling older adults over 65 years of age, who respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The analysis of the number of organizations revealed the HRs of the number of types of organizations progressively decreased as the number of participating organizations. This supports previous studies, including those measuring other health outcomes [10,13,[16][17][18]. In this study, HRs were lower when participated in two or more types of organizations in rural areas than in urban areas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The analysis of the number of organizations revealed the HRs of the number of types of organizations progressively decreased as the number of participating organizations. This supports previous studies, including those measuring other health outcomes [10,13,[16][17][18]. In this study, HRs were lower when participated in two or more types of organizations in rural areas than in urban areas.…”
Section: Discussionsupporting
confidence: 91%
“…In many longitudinal studies, social participation has been reported as effective for health outcomes such as functional disability [9][10][11][12][13], cognitive disability [14][15][16], instrumental activities of daily living decline [17][18][19], and basic activities of daily living decline [20]. Among them, some studies focused on the number and types of organizations in which older people participated [10,13,[16][17][18]. These studies suggested that older people who participate in more organizations are healthier than those who do not participate, and that the relationships between social participation and health varied according to the types of organization they participate in.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that social participation decreases stress levels . In addition, social participation might prevent dementia onset and functional decline; and social participation greatly improves quality of life in older people …”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported that social participation decreases stress levels. 1 In addition, social participation might prevent dementia onset and functional decline; [2][3][4] and social participation greatly improves quality of life in older people. 5 According to a Japanese national survey, a substantial number of individuals who are currently non-participants in social groups are willing to engage in social groups.…”
Section: Introductionmentioning
confidence: 99%